DEFENCE OF DOMINANT UNDERTAKING - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Abuse of dominance is prohibited. However, exclusionary conduct of dominant undertaking may escape prohibition under Article 102 of the Treaty on the Functioning of the European Union if the dominant firm can prove that there is a justification for its actions.The subject matter of this paper is the analysis of possible defences of a dominant firm, as well as identification of theoretical and practical problems relating to the defence of dominant undertaking in the competition law of the European Union.
Keywords: Keywords: dominant position on a market, abuse of dominance, objective justification, objective necessity, efficiencies.